Nano-technological aspects of zinc oxide and silver in cosmetics - Shamaila, S.; Jalil, Ayesha; Ishfaq, Muhammad; Sharif, R. (Journal of applied physics, 2022)
Nanoparticles (NPs) specifically synthesized from leaves’ extracts with a high content of phytonutrients have gained significant importance in personal care products such as sunscreens. The objective of this study was to estimate the in vitro sunscreen activity of an emulsion comprising ZnO and Ag NPs synthesized with the leaves’ extract of Laurus nobilis and Citrus limon based on their stability and capping agents. The sun protection factor (SPF) of cream emulsion containing ZnO and Ag NPs was assessed by an ultraviolet spectrophotometric process along with the Mansur equation. At certain and controlled parameters, the synthesized NPs were finely characterized by ultraviolet–visible spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and an energy-dispersive x-ray spectroscopy technique followed by analyzing some physicochemical parameters such as the hydrogen ion concentration (pH), stability test, viscosity analysis, irritancy patch test, and physical texture verification. The SPF values of the cream emulsion containing ZnO and Ag NPs were recorded as 0.573 and 0.601, respectively. The concentrations of hydrogen ion (pH) of the cream emulsion were 5.5 and 6.3 and are according to the nature of skin. Viscosity summary for the cream emulsion specified comparable rheology, which is considered a basic trait for the emulsion. The emulsion was found stable as there was no phase segregation and liquefaction was detected after centrifugation. Obtaining innovative results that have been concluded from experiments showed that the cream emulsion has photo-protective action and may be employed to improve cosmetics formulation that can be explored as profitable commercial products.